ANALISIS PUBLIC SERVICE MOTIVATION DAN KORELASINYA DENGAN KONSEP ALTRUISME - Budy Mulyawan; Muhamad Ali Embi (Journal of Administration and International Development, 2022)
Many previous studies have found that employee performance can be influenced by their motivation. One of the intrinsic motivations that are believed to have an influence on employee performance is public service motivation. In this study, the concept of altruism will be represented by one of its dimensions, namely the belief in a just world dimension. The objective of this study is to analyze the correlation and influence of belief in a just world on public service motivation among civil servants in Jakarta. The research was carried out using quantitative method and also literature rule as an analytical tool. Respondents in this study were 951 civil servants who came from 3 agencies with the highest incomes in Jakarta, the DKI Jakarta Provincial Government, the Directorate General of Taxes and the Directorate General of Immigration. The results of the study show that the belief in a just world dimension has a significant correlation and influence on the level of public service motivation, besides that this dimension is suitable to be applied as an additional dimension of public service motivation from Perry and Wise (1990) to measure the level of public service motivation of employees in Indonesia.